Deciphering the Concept of Goodness in Islam: A Comprehensive Qur’anic Linguistic and Thematic Analysis - Zainuddin, Zainuddin (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
This article delves into the concept of “goodness” (al-khair) within Islamic teachings as interpreted from the Qur’an, exploring its nuanced and context-dependent meanings. Al-khair in Arabic signifies all that is good and beneficial, standing in contrast to al-syar, which represents evil and wrongdoing. This study employs a descriptive-analytical qualitative approach, utilizing a detailed examination of Qur’anic verses, Tafsir literature, and Hadiths to unravel the layered meanings of al-khair. Our findings highlight that al-khair not only encompasses moral and social virtues but also material aspects such as wealth and physical well-being. The term is comparable to thayyibun, husnun, birrun, and ma’ruffun in the Qur’an, each carrying distinct but sometimes overlapping meanings. The analysis distinguishes three key dimensions of al-khair: the ultimate good deeds chosen for humanity, the commendable acts ordained by Allah, and attributes often associated with Allah’s characteristics. The study concludes that while goodness is generally perceived as desirable, its interpretation can vary significantly, leading to both positive and negative outcomes depending on the context.